Total syntheses of echinopines A and B, sesquiterpenes with a unique tetracyclic [3-5-5-7] skeleton. Issue 24 (16th June 2016) - Sanogo, Youssouf; Allievi, Luca; Lecourt, Camille; Dhambri, Sabrina; Ardisson, Janick; Sorin, Geoffroy; Lannou, Marie-Isabelle
Graphical abstract: